Lower Bound of Blow up Time for Three Species Cooperating Model - Bhuvaneswari, V.; Balachandran, K. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we consider the initial boundary value problem for the three species cooperating model under various boundary conditions in which the solution may blow up in finite time. Explicit lower bound for blow up time is being obtained by using techniques based on Sobolev type and first order differential inequalities.